“All hands on deck” – rota-lithotripsy – a combination of rotational atherectomy and intravascular lithotripsy (shockwave) with additional use of a Turnpike Gold microcatheter and guide extension as a novel approach for calcified lesions - Rola, Piotr; Włodarczak, Adrian; Barycki, Matuesz; J. Kulczycki, Jan; Engel, Barbara; Doroszko, Adrian (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
The progress of the aging process in the general population and increase in the number of comorbidities in elderly people make the success of interventional cardiology treatments increasingly challenging. Alongside increased lifespan, we observe a growing number of complex percutaneous coronary interventions (PCI) performed in everyday practice. The procedures are inextricably associated with increased prevalence of patients with heavily calcified lesions which may affect the periprocedural complication and revascularization failure rate and – as a result – the short- and long-term survival [1]. Additionally, unfavorable coronary anatomy (tortuosity, angulation, presence of major side branch, and excessive calcium deposits) commonly complicate the use of sophisticated maneuvers and dedicated technologies to perform a successful PCI. Atherectomy devices have been widely used as safe and efficient tools to modify plaque calcium burden plaque [2]. Nevertheless, rotational atherectomy (RA) is associated with a substantial risk of complications such as perforation, short-term closure, side branch loss, and the slow-flow/no-reflow phenomenon, vasospasm, and burr entrapment [3] and requires appropriate operator’s training. A recent study [4] suggested that shockwave intravascular lithotripsy (S-IVL) might be a simple, safe, and effective alternative method aiming at modification of heavily calcified lesions. The Shockwave Medical Intravascular Lithotripsy System (Shockwave Medical Inc., Fremont, United States) delivers sonic pressure waves during low-pressure balloon inflation, which affects mainly calcifications, leading to fragmentation of calcium nodules. In this paper we present a novel method – rota-lithotripsy – which combines the two plaque modification techniques RA and S-IVL with the additional use of uncustomary maneuvers and hardware, to deal with an undilatable calcified lesion.